Question

Match each quadratic function given in factored form with its equivalent standard form listed on the left. f(x) = (x 2)(x – 6) f(x) = (x – 4)(x 3) f(x) = (x – 12)(x 1) f(x) = (x – 3)(x 4)

1. thachthao
standard form of the given equation are
-f(*) = (x + 2)(x – 6) = x² – 4x – 12
f(x) = (x – 4)(x + 3) = x² – x – 12
f(x) = (x – 12)(x + 1) = x² – 11x – 12
f(x) = (x -3)(x + 4) = x² + x – 12

A polynomial function with one or more variables in which the second-degree term is the highest degree is known as a quadratic function, quadratic polynomial, polynomial of degree 2, or simply a quadratic, in algebra.

### What is standard form of a quadratic function?

As long as an is not equal to zero, the quadratic function f(x) = a(x – h)2 + k is considered to be in standard form. The graph starts out in either an upward or a downward direction depending on the value of a. The point at the vertex of the symmetry is represented by the vertical line x = h. (h,k).

### According to the given information:

The standard form list.
1 .   (x + 2)(x – 6)
= x² – 6x + 2x – 12
=  x² – 4x -12
2.  (x – 4)(x + 3)
= x² + 3x – 4x – 12
=   x² – x – 12
3. (x – 12)(x + 1)
= x² + 1x – 12x – 12
=  x² – 11x – 12
4.  (x -3)(x + 4)
=   x² + 4x – 3x – 12
= x² + x – 12
So the equivalent standard form  of the give values are :
-f(*) = (x + 2)(x – 6) = x² – 4x – 12
f(x) = (x – 4)(x + 3) = x² – x – 12
f(x) = (x – 12)(x + 1) =  x² – 11x – 12
f(x) = (x -3)(x + 4) = x² + x – 12